Challenges for Implementation in Diverse Settings: reflections on two randomised controlled trials of educational interventions in South American communities - Mesa, C; Puglisi, M; Nag, S; Newbury, D; Hulme, C; Snowling, M (SAGE Publications, 2022)
Research in the UK suggests that multi-componential interventions focusing on language and pre-literacy skills can improve children’s reading and language skills. However, simple translations of such programmes may not produce equivalent effects in diverse communities. The reasons for this are multi-faceted and include factors beyond the rationale and content of the intervention programmes themselves. Understanding these factors is critical for creating programmes that will generalise across settings. In this review, we reflect upon challenges encountered in two reading and language intervention programmes in South America to identify community and cultural contextual factors that can influence the implementation and scalability of educational programmes. We use our findings to develop an education-specific framework to guide the development and implementation of high-quality evidence-based approaches to language and literacy intervention. Our model guides implementation practices in diverse contexts and stresses the importance of the evidence-base and communication.